COVID-19 information seeking: a survey of residents of Chilinde and Chinsapo Townships in Malawi - Wella, Kondwani; Mtambo, Jim; Lazaro, Matthews (South African Journal of Libraries and Information Science (SAJLIS), 2024)
The Coronavirus Disease 2019 (COVID-19) outbreak spread anxiety among the general public, which was exacerbated by an excessive amount of misleading information. This study investigated the behaviour of Chilinde and Chinsapo residents in seeking COVID-19 information. The study used a quantitative research approach, whereby a modified Health Information National Trends Survey (HINTS) questionnaire was used to collect data from 627 participants. Descriptive statistics were used to summarise the characteristics of the study participants and the sources and types of COVID-19 information used. Most of the participants (71.3%, n=447) reported that they had looked for information about COVID-19 from different sources. Doctors and healthcare providers were the main sources of information on COVID-19. There were 58.1% (n=364) of participants who indicated that they were extremely worried about getting infected with COVID-19. It was further found that there was limited use of online platforms to access COVID-19 information. Multiple logistic regression results showed that male respondents had a higher chance of having online access to COVID-19 information than their female counterparts. Chilinde participants were more likely to have online access, unlike those residing in Chinsapo. This study recommends raising awareness to the masses regarding the use of reputable online sources in crisis situations in the future.
Keywords: COVID-19; Malawi; information seeking